(3MGTjI Ydi eYGde GdOjfs - (3GdTQhGfj, GdejQRG GdTQhGfj, GdTQhGfj, eMeO Hf GdMSf GdTQhGfj GdCUagGfj, J (B1099(3g` (B1688(3es
(3ChdgG (B:s
(3ChdgG(B: (3Gdabg aj GddZI Gdage, hGfeG GHJOC HJYQja Gdabg Ohf CUhd Gdabgs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg(B: (3jbJVj EdZGA GdNGU gPG eHfj Ydi YOe LhGR GdfSg bHd MVhQ hbJ GdYed HGdefShN hEdG jchf fSkNG Ydi GdJbOjQ ef cPG bd hdYdg GLed GYJeGOGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B6: 90s
(3GdPQjYI, L (B6: 58(3, (B153s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs